Effect of follicle size in nuclear and cytoplasmic maturation of oocytes from zebu cows - Dode, Margot Alves Nunes; Rodovalho, Norma Cleá; Ueno, Vanessa Gomes; Alves, Rafael Geraldo de Oliveira (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this study was to investigate the effect of follicle size on the ability of the oocytes to undergo nuclear and cytoplasmic maturation. Ovaries from Nelore cows (Bos indicus) were collected just after slaughter. The cumulus oocyte complexes were aspirated from four size categories follicles: 1-2 mm, 3-5 mm, 6-8 mm and ≥ 9 mm of diameter. The oocytes were measured and evaluated for chromatin configuration before maturation. After selection the oocytes were matured, fertilized and cultured in vitro. Oocytes obtained from follicles of 1-2 mm showed a smaller diameter (P < 0.01) than the other follicle groups. Before maturation 89.8%, 90.1%, 85.7% and 100% of oocytes from follicles of 1-2 mm, 3-5 mm, 6-8 mm and ≥ 9 mm, respectively, showed a germinal vesicle. A similar maturation rate (P < 0.05) was observed for all groups, with 88.8%, 87.8%, 92.9% and 100.0% of the oocytes in metaphase II for follicles of 1-2, 3-5, 6-8 and ≥ 9 mm, respectively. The penetration and clivage rates were also similar (P > 0.05) for oocytes obtained from follicle of 1-2 mm (93.4% and 81.9%), 3-5 mm (90.7% and 79.6%), 6-8 mm (91.3% and 77.8%) and ³ 9 mm (92.0% and 78.3%). In addition, there were no differences (P > 0.05) among follicles groups on the percentage of oocytes showing polispermy, decondensed sperm head and pronuclei formation. The results of this experiment showed that oocytes obtained from 1-2 mm to ≥ 9 mm follicles, from Bos indicus, have similar capability to undergo in vitro maturation and fertilization as the larger follicles.